Teachers’ Skill in Utilizing Literary Texts to Train Students’ Critical Thinking - Nurhajati, Diani; Susanti, Yunik; Kencanawati, Dewi (Jurnal Pendidikan Guru Sekolah Dasar, 2025)
One of dimension in Pancasila Student Profile is students have ability to think critically. Teachers can apply many strategies to train their students in order that their critical thinking develop. One of them is by utilizing literary text in teaching. This research aims to describe the skills of elementary school teachers in utilizing literary text to train critical thinking to the students. This research applies a descriptive qualitative approach in which the subjects of this research were 1 school principal, 2 teachers of grades 5 and 6, and 40 students of SDN 1 Loceret, Nganjuk. The researcher used guided interview, questionnaires, and document analysis to collect the data. The finding of the research can be described that the teachers have already used local literary text, such as poems and short stories to train critical thinking skills. They used those texts for teaching materials. However, they still had problems to develop activities that train the students to think critically. They only utilize those texts in curricular activity or during the teaching-learning in the classroom. It is recommended that teachers should utilize the local-culture based stories in co-curricular and extra-curricular.